2020
DOI: 10.3389/fimmu.2020.00381
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Differential Processing of HLA Class II-Restricted Minor Histocompatibility Antigen LB-PIP4K2A-1S and Its Allelic Variant by Asparagine Endopeptidase

Abstract: Minor histocompatibility antigens are the main targets of donor-derived T-cells after allogeneic stem cell transplantation. Identification of these antigens and understanding their biology are a key requisite for more insight into how graft vs. leukemia effect and graft vs. host disease could be separated. We here identified four new HLA class II-restricted minor histocompatibility antigens using whole genome association scanning. For one of the new antigens, i.e., LB-PIP4K2A-1S, we measured strong T-cell reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Using mass spectrometry, we validated a total of 24 novel GvL mHAs, an increase from the 13 GvL mHAs that have been discovered since Els Goulmy et al reported the first discovered GvL mHA, HA-1, in 1983 1,25,28,[30][31][32][33] . The 16 novel GvL mHAs found for HLA-A*02:01 together cover 98.8% of HLA-A*02:01-positive patients in the DISCOVeRY-BMT dataset, the three for HLA-B*35:01 cover 60.7% of HLA-B*35-:01-positive DISCOVeRY-BMT patients, and the five for HLA-C*07:02 cover 78.9% of HLA-C*07:02-positive DISCOVeRY-BMT patients.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Using mass spectrometry, we validated a total of 24 novel GvL mHAs, an increase from the 13 GvL mHAs that have been discovered since Els Goulmy et al reported the first discovered GvL mHA, HA-1, in 1983 1,25,28,[30][31][32][33] . The 16 novel GvL mHAs found for HLA-A*02:01 together cover 98.8% of HLA-A*02:01-positive patients in the DISCOVeRY-BMT dataset, the three for HLA-B*35:01 cover 60.7% of HLA-B*35-:01-positive DISCOVeRY-BMT patients, and the five for HLA-C*07:02 cover 78.9% of HLA-C*07:02-positive DISCOVeRY-BMT patients.…”
Section: Discussionmentioning
confidence: 97%
“…The copyright holder for this preprint this version posted August 15, 2022. ; https://doi.org/10.1101/2022.08.12.503667 doi: bioRxiv preprint cell responses against them will lead to GvL effects without GvHD. Approximately 55 mHAs have been reported to date, including 13 validated GvL mHAs, and clinical trials of mHA-targeted cellular immunotherapies and vaccines have been performed [25][26][27][28][29][30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore advisable to test T-cell recognition of the wt version to at least avoid cross-reactivity on use of a neoepitope-based vaccine or T-cell transfer. In regard to CARS2, which shows a limited amount of cross-reactivity against the wt epitope, we suggest that for this particular antigen, discrimination between the mutated and wt antigen be determined by differential processing, [42][43][44] because retroviral expression of full-length CARS2 in MCF-7 cells did not lead to T-cell recognition and exposure of APCs to tumor cell lysates resulted in specific presentation of mutant CARS2.…”
Section: Open Accessmentioning
confidence: 96%
“…Recently, SNP-induced differential processing was also found for an HLA-II restricted minor H antigen (95), indicating that development of HLA-II epitope processing prediction algorithms may be valuable for future identification of immunogenic HLA-II presented antigens.…”
Section: Differential Peptide Processing and Presentation Is A Major mentioning
confidence: 99%